Interface formation and bonding mechanisms of laser transmission welded composite structure of PET on austenitic steel via beam oscillation. (1st March 2020) - Hao, Kangda; Liao, Wei; Zhang, Tiedong; Gao, Ming
Abstract: Laser lap welding of composite structure of amorphous polyethylene terephthalate (PET) to 304 steel was carried out via beam oscillation. The effects of laser power (P), oscillating radius (r) and frequency (f) on weld macroscopic morphologies, tensile properties and bonding mechanisms were investigated. The defect of thermal degradation could be eliminated, but the lack of fusion occurred with the r approaching 3 mm. The welds were homogeneous with the pores discretely or network distributed when the r was between 2 and 2.5 mm. The bonding strength increased from the center to the edge with more retained base steel on the PET surface. The welding parameters were optimized as the P of 300 W, the r of 2 mm, the f of 300 Hz under given welding speed of 50 cm/min and defocused distance of 20 mm. The shear force was 26% higher than the sample without beam oscillation, because of the C-M and C-O formed by the reactions of the PET with the steel and the air. The weld homogeneity was illustrated on the basis of the proposed energy distribution model. The formation and inhibition mechanisms of the thermal degradation and lack of fusion were then discussed.